2021
DOI: 10.1111/eff.12568
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the seasonal migration of Round Goby (Neogobius melanostomus, Pallas 1814) and implications for the Lake Ontario food web

Abstract: Seasonal habitat shifts are a common phenomenon in fish life histories, with numerous species moving seasonally to spatially disjunct sites for a wide range of activities like breeding, overwintering, juvenile development or summer feeding (Burton & Burton, 2018). The cues and senses used by fish to initiate and maintain seasonal movements vary considerably across species, but most commonly include some combination of temperature, light and olfaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…This ultimately reveals a pronounced seasonal migration between shallow coastal waters and offshore areas, which can be related directly to different thermal conditions between the seasons. This finding mirrors the annual inshore/offshore seasonal migration of round goby documented in some North American lakes (Andres et al 2020, Pennuto et al 2021) and previously suggested in Europe (Sapota and Skora 2005;Christoffersen et al 2019). These migration events have been shown to translocate significant amounts of energy, prey, and nutrients in a range of lake sizes (Johnson et al 2005, Andres et al 2020, Pennuto et al 2021.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This ultimately reveals a pronounced seasonal migration between shallow coastal waters and offshore areas, which can be related directly to different thermal conditions between the seasons. This finding mirrors the annual inshore/offshore seasonal migration of round goby documented in some North American lakes (Andres et al 2020, Pennuto et al 2021) and previously suggested in Europe (Sapota and Skora 2005;Christoffersen et al 2019). These migration events have been shown to translocate significant amounts of energy, prey, and nutrients in a range of lake sizes (Johnson et al 2005, Andres et al 2020, Pennuto et al 2021.…”
Section: Discussionsupporting
confidence: 89%
“…This finding mirrors the annual inshore/offshore seasonal migration of round goby documented in some North American lakes (Andres et al 2020, Pennuto et al 2021) and previously suggested in Europe (Sapota and Skora 2005;Christoffersen et al 2019). These migration events have been shown to translocate significant amounts of energy, prey, and nutrients in a range of lake sizes (Johnson et al 2005, Andres et al 2020, Pennuto et al 2021. ECThe deepest location previously recorded was 130 m in the North American Great Lakes (Walsh et al 2007) (although based on much less extensive spatial data), as opposed to 90 m in the Baltic Sea in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations